Cardiac electrophysiological experiments in numero, part iii: simulation of arrhythmias and pacing. - Malik M; Camm J (Pacing & Clinical Electrophysiology, 1991)
This paper is the third and final part of a series of articles reviewing mathematical and computer models of the electrophysiological processes. This section reviews the arrhythmia simulation and discusses models of arrhythmogenic processes, fibrillation and defibrillation, and of heart-pacemaker interaction. The models of arrhythmogenesis are classified into three main sections: models of reentry and vortex reentry, models of myocardial electrotonic interactions, and models of macroreentrant supraventricular tachycardias. This final part of the review discusses the future potential of mathematical and computer models of different cardiac processes.